Investigating the degradation of phenols by aerobic thermophilic bacteria - Mol, Bronwyn (My University, 2020)
Phenol and its derivatives are toxic aromatic hydrocarbons frequently found to contaminate industrial and agricultural wastewaters. Bacterial whole-cell biodegradation is a frequently employed technique for phenol removal as it is environmentally friendly, cost effective and allows for the complete mineralisation of phenol. A promising avenue of research is the use of aerobic thermophilic bacteria for phenol bioremediation. Advantages of high temperature bioremediation strategies include increased phenol solubility at higher temperatures as well faster biomass production and phenol degradation rates in thermophilic bacteria. This study aimed to identify and characterise aerobic thermophilic bacteria which are able to survive in the presence of phenol and actively degrade high concentrations of phenol. Chapter 1 presents a review of the pertinent literature pertaining to phenols, their environmental effects, mechanisms for their degradation and the pathways utilised by microbial phenol degraders. In Chapter 2 an extensive culture of thermophilic bacteria was screened for the capacity for resistance to phenol toxicity and phenol degradation. A number of taxa tolerant to high concentrations (up to 1,200 mg/l) of phenol were identified. Subsequently, in Chapter 3 the most proficient phenol degrading strain, Bacillus smithii Row 2A12.3A was further characterized through genome sequencing and comparative genomic analysis. The molecular determinants underlying its capacity for phenol degradation were determined in silico
A dissertation submitted in fulfilment of the requirements for the degree Master of Science in Molecular and Cell Biology in the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa, 2020
Keywords: Phenols; Thermophilic microorganisms